Aging Detection of Glass Disc Insulator by using Infrared Camera - Mohammed Imran Mousa; Zulkurnain Abdul-Malek; Zainab Imran Mousa (Institute of Advanced Engineering and Science, 2017)
Suitable diagnostic techniques for outdoor glass insulators are important for ensuring the reliablilty and stability of power system. The possibility of insulator flash-over increases, especially when the insulator is covered by pollution layers or has an internal defect. In this paper, a new technique to detect the pollution level and invisible damage by measuring the surface temperature of glass disc insulators is proposed. A high definition camera had been used to determine the surface temperatures of four glass insulators. The effects of applied voltage on the surface temperature and its distribution were studied. The results show the possibility of using the infrarad camera to detect the aging level and invisible damages of the glass insulators.